Making Sense of Archives: An Introduction - Lučić Iva (Comparative Southeast European Studies)
This introduction to the thematic section “Making Sense of Archives” explores different archival terrains in Southeastern Europe. It discusses the politics of storage against the background of the processes of professionalization in the archival field, the provenance of funding for both storing and digitalizing archival collections, and the chronic lack of archival personnel. The author makes a plea for critical engagement with archival spaces by explicating the logics of the archiving processes of documents of different kinds and the dimensions of power immanent to them. Moreover, she argues that scholars need to reflect more critically on archivists’ mediating interventions, including appraisal, arrangement, processing, and description as a necessary complement to applied source criticism. Lastly, she locates the thematic section’s contributions within broader themes in the archival field, including knowledge management and blind spots in archives, the archival turn, the potentials and pitfalls of visual archives, and the study of documents as archival artefacts.